Significance of Concept Mapping in Reading Literacy - novianty, melisa (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2021)
the current issue of significant concern that many countries define literacy as the ability to read and/ or write simple statement in either a national or native language. In fact, the learning of English literacy has been developing in many definitions by different opinions and different countries in the world. Some researchers reported the understanding of being and becoming literate must be shows how variants of it into policy discourse. This paper highlights the significance of concept mapping in reading literacy. As addition, in this context that reading literacy will be used by using concept maps then it can be designed by pictures, circles or boxs after reading the text depend on the ways of thinking and the creativity in create it.